Towards a Cultural Value of Design and Democracy - Bryan Bell (Oz, 2013)
In October of 2000 Design Corps held a conference at Princeton University called Structures for Inclusion and made the challenge that we should “design for the 98% who were currently un-served by architects.” This slogan has served as a rallying cry for a growing Public Interest Design movement over the last 13 years.